2022
DOI: 10.1002/lio2.956
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and mycological investigations of post‐COVID‐19 acute invasive fungal sinusitis

Abstract: Objectives An increased incidence of acute invasive fungal sinusitis associated with the recent COVID‐19 pandemic has been observed, which is considered a public health concern. This study aims to detect the incidence, risk factors, causative agents, clinical presentations, outcomes, and susceptibility rate of various antifungals. Methods In this cross‐sectional cohort study, a total of 30 patients showing acute invasive fungal rhinosinusitis following a COVID‐19 infection were investigated. Histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Human and animal model studies have concluded that, in addition to diabetes, being immunocompromised is another key factor that makes individuals more susceptible to mucormycosis [6,26,27]. Long before the COVID-19 pandemic, corticosteroids were recognized as a risk factor for opportunistic fungal infections like mucormycosis due to their complex immunosuppressant effects [28].…”
Section: Discussionmentioning
confidence: 99%
“…Human and animal model studies have concluded that, in addition to diabetes, being immunocompromised is another key factor that makes individuals more susceptible to mucormycosis [6,26,27]. Long before the COVID-19 pandemic, corticosteroids were recognized as a risk factor for opportunistic fungal infections like mucormycosis due to their complex immunosuppressant effects [28].…”
Section: Discussionmentioning
confidence: 99%